1998
DOI: 10.1183/09031936.98.12040926
|View full text |Cite
|
Sign up to set email alerts
|

Expression of three members of the TNF-R family of receptors (4-1BB, lymphotoxin-beta receptor, and Fas) in human lung

Abstract: Receptors belonging to the tumour necrosis factor receptor (TNF-R) superfamily are implicated in a variety of important biological processes. Although messenger ribonucleic acid coding for many of these receptors has been detected in lung, little is known about their expression in this organ. In this study, immunohistochemical techniques were used to evaluate the expression of three receptors of this family (4-1BB, lymphotoxin-beta receptor (LTbeta-R), and Fas) in normal human lung, lung carcinomas and by tube… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
20
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 31 publications
(41 reference statements)
3
20
1
Order By: Relevance
“…The images show that LThR expression is not restricted to the tumor compartments but can also be detected in the normal breast ductal epithelial cells as well as in the normal colon epithelium. These observations were in agreement with a previous study showing expression of LThR in lung carcinomas and in hyperplastic bronchial lining cells (30). Based on these findings, the high frequency of LThR expression in a broad range of solid tumors suggests tumors of diverse tissue origins and histotypes as potential additional candidates for CBE11 therapy.…”
Section: Staining For Cd3supporting
confidence: 93%
“…The images show that LThR expression is not restricted to the tumor compartments but can also be detected in the normal breast ductal epithelial cells as well as in the normal colon epithelium. These observations were in agreement with a previous study showing expression of LThR in lung carcinomas and in hyperplastic bronchial lining cells (30). Based on these findings, the high frequency of LThR expression in a broad range of solid tumors suggests tumors of diverse tissue origins and histotypes as potential additional candidates for CBE11 therapy.…”
Section: Staining For Cd3supporting
confidence: 93%
“…Direct comparison by FACS of fetal and adult intestines confirmed that LT␤R expression is higher in the fetus and begins to decrease at birth. This observation is interesting since many human breast and colorectal carcinomas are LT␤R bright by immunohistochemical staining while much of the surrounding nontransformed stromal tissue is receptor dull (J. Browning, V. Bailly, and S. Violette, unpublished data) and a similar observation was reported for lung carcinomas (44). Therefore, in some epithelial layers, surface LT␤R is displayed during development and perhaps some carcinomas recapitulate ontology by reinstating the higher fetal level of surface expression.…”
Section: Discussionmentioning
confidence: 56%
“…We investigated five apoptosis-associated proteins in NSCLC tissues, namely bcl-2, caspase-3, fas, fasL, and survivin. According to data updates, these proteins may be important for the balance of cell proliferation and cell death to maintain cellular homeostasis in normal lung tissues [24][25][26][27][28]. But their actual roles in can-236 236 236 236 236 In the current study, we found bcl-2, which was originally cloned from the t(14;18) translocation breakpoint found in follicular B-cell lymphomas, to be related to large tumor size in NSCLC.…”
mentioning
confidence: 76%